Fibroblast growth factor regulation of neovascularization - Murakami, Masahiro; Simons, Michael (Current opinion in hematology, 2008)
Fibroblast growth factors are potent angiogenic inducers; however, their precise roles in angiogenesis have not been well understood. In this review, we will focus on specific roles played by fibroblast growth factors in neovascularization. Although fibroblast growth factors promote a strong angiogenic response, it has been suggested that FGF-induced angiogenesis requires activation of the vascular endothelial growth factor system. Recent findings have endorsed the view of indirect contribution of fibroblast growth factor signaling to vascular development. A study using embryoid bodies demonstrated a nonimmediate role played by fibrobalst growth factor receptor 1 in vasculogenesis as vascular endothelial growth factor supplementation was sufficient to promote vascular development in Fgfr1-/- embryoid bodies. Moreover, another line of evidence indicated that myocardial fibroblast growth factor signaling is essential for mouse coronary development. The key role of fibroblast growth factor signaling in this process is Hedgehog activation, which induces vascular endothelial growth factor expression and formation of the coronary vasculature. In addition to vascular endothelial growth factor interaction, fibroblast growth factors can control neovascularization by influencing other growth factors and chemokines such as platelet-derived growth factor, hepatocyte growth factor and monocyte chemoattractant protein-1, contributing to development of mature vessels and collateral arteries. Although fibroblast growth factors are potent angiogenic factors, they may indirectly control neovascularization in concert with other growth factors. Thus, the unique role played by fibroblast growth factors might be organization of various angiogenic pathways and coordination of cell-cell interactions in this process.